2016
DOI: 10.1136/bmjspcare-2015-001085
|View full text |Cite
|
Sign up to set email alerts
|

Good concordance between patients and their non-professional carers about factors associated with a ‘good death’ and other important end-of-life decisions

Abstract: When discussions around end-of-life choices do occur, carers generally appear to agree with the patients' preferences around end-of-life treatment, and preferred place of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 23 publications
0
28
0
4
Order By: Relevance
“…Locality was also identified as a critical element, with deaths and dying ideally to be connected with the rural/remote community. The literature increasingly reports that place of death is one measure of a contemporary 'good death' as supported by the majority of articles in this review; however as Biggs (2014) suggests, place is only one factor of importance and not necessarily the main one for all people (Hoare et al 2015, Davies et al 2016, Rainsford et al 2016). If it is not possible to die at home surrounded by family then it is important to die within the rural community.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Locality was also identified as a critical element, with deaths and dying ideally to be connected with the rural/remote community. The literature increasingly reports that place of death is one measure of a contemporary 'good death' as supported by the majority of articles in this review; however as Biggs (2014) suggests, place is only one factor of importance and not necessarily the main one for all people (Hoare et al 2015, Davies et al 2016, Rainsford et al 2016). If it is not possible to die at home surrounded by family then it is important to die within the rural community.…”
Section: Discussionmentioning
confidence: 63%
“…Despite the challenges of rural definition, and notwithstanding differences in rural locations, cultural perspectives, priorities and expectations, this scoping review found similarities and differences in perspectives with those reported in urban studies. The four elements (physical, spiritual, emotional and social) considered essential by the WHO (2015) to facilitate a 'good death' were identified as pain/symptom control, dignity, preparedness, autonomy and community and are consistent with urban findings (Holdsworth 2015, Raisio et al 2015, Davies et al 2016, Meier et al 2016. However, the context and priority placed on each factor differed between included studies and from urban perspectives (Kirby et al 2016).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…where patient wants to die). As choices at the end‐of‐life are complex and multi‐layered, agreement across the range of domains that can influence quality of death and dying, such as involvement in decision‐making, type and location of care, should be established …”
Section: Introductionmentioning
confidence: 99%